Efektivitas Penggunaan E-wallet sebagai Alat Transaksi Pembayaran Pengganti Uang Tunai - Aida Dewi Amalia; Dwi Wahyuni (Lembaga Yasin AlSys, 2026)
The development of financial technology has driven the transformation of payment systems from cash transactions to digital transactions, including the use of e-wallets in the micro, small, and medium enterprise (MSME) sector. However, the adoption of this technology still faces various challenges, making it necessary to examine the effectiveness of its use in supporting community economic activities. This study aims to analyze the effectiveness of using e-wallets as payment transaction instruments replacing cash in MSMEs in Peterongan Village. This study used a qualitative approach with a descriptive method. The research subjects consisted of seven MSME actors and several buyers selected through purposive sampling based on the criterion of being active e-wallet users in business transaction activities. Data were collected through structured interviews, observation, and documentation, then analyzed using the interactive analysis model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The field research was conducted in 2026 for approximately two months. The results of the study show that the use of e-wallets among MSMEs in Peterongan Village is effective based on five main indicators, namely ease of use, transaction speed, transaction security, accuracy of financial data recording, and efficiency in business financial management. E-wallets were considered easy to use because they have a simple interface and are supported by the QRIS feature. In addition, transactions were fast, secure, and recorded automatically and accurately. The conclusion of the study affirms that the use of e-wallets is effective as an alternative payment instrument replacing cash in MSMEs. The implications of this study indicate that the use of e-wallets can support operational efficiency, strengthen financial recording, and encourage digital transformation in the MSME sector at the village level.